Upscaling Hydrological Processes for Land Surface Models With a Two‐Hydrologic‐Variable Model: Application to the Little Washita Watershed. Issue 9 (1st September 2022) - Picourlat, Fanny; Mouche, Emmanuel; Mügler, Claude
Abstract: Land Surface Models (LSMs) are key components of Earth System Models, which the Intergovernmental Panel on Climate Change relies on in many of their studies. However, these models either neglect or oversimplify basin‐scale hydrological processes that produce the land surface water balance. Bringing the dominant physical processes from the local scale up to the LSMs presents a significant challenge for improving the models. This article presents an upscaling (or bottom‐up) approach to identify the basin‐scale driving variables that need to be exported into LSMs. The approach is developed on the Little Washita Watershed (OK, USA) using 20‐year hydrology (1993–2013). A physically based 3D model built with HydroGeoSphere first produces a reference simulation. An equivalent hillslope model is then able to capture both 3D simulated water balance and local water table dynamics with reasonable accuracy. The physical analysis of the water balance in the different hillslope compartments leads to the identification of two driving variables: seepage face extension and water table slope. The two variables are then implemented in a conceptual model. Results show a good capacity of this model to capture the water balance of hillslopes having different lengths and slopes. Moreover, the model is able to capture the water balance of the reference simulation with reasonable accuracy. The proposed approach thus reduces the 3D watershed model to a two‐variable conceptual model that constitutes a basis for developing an improved LSM hydrology. Key Points: An upscaling approach reduces model dimensionality from 3D watershed to 2D equivalent hillslope, and then to a two‐hydrologic‐variable model The seepage face extension and the water table slope are identified as two key variables The approach is validated on the 20‐year hydrology (1993–2013) of the Little Washita Watershed (Ok, USA)